Scoping Sustainability Practices in Higher Education Institutions: A Bibliometric and Systematic Review (Prithvi Academic Journal, 2025)
The standing of higher education institutions (HEIs) and their role in shaping the societal mind-set is crucial in promoting sustainable human behavior. Considered as the microsom of the broader societal setting, incorporating sustainability practices (SP) within institution is equally important, beyond merely teaching the courses. HEIs have been taking SP for long, though the degree of informed approaches was low in the past. However, in recent years the concept has become more informed and systematic and the subject is attracting researchers across the world. Thus, this study explores the scope of SP in HEIs worldwide, offering insights into strategies, trends, and gaps. For this, a total 964 articles have been considered for the bibliometric analysis and 44 peer-reviewed articles for systematic review, published between the year 2014 to 2023. The study identifies key dimensions and benchmarks of HEIs in embracing sustainable development. Using bibliometric analysis and thematic synthesis, the result highlights a significant increase in sustainability research, with 2023 marking a notable peak. Likewise, the systematic review exhibit an enormous evaluation of sustainability initiatives in HEIs from scattered efforts to integrative, campus-wide sustainability models. As strong as environmental, social and economic sustainability initiatives have been established, their inclination towards integration reinforces their long-term impacts. Balancing short-term institutional needs and overall sustainability objectives, however, remains problematic.